A Case of Amoxicillin-Induced Acute Generalized Exanthematous Pustulosis Presenting as Septic Shock. Issue 4 (July 2017) - McDonald, Katherine A.; Pierscianowski, Tadeusz A.
This case report demonstrates the challenges of diagnosing and managing acute generalized exanthematous pustulosis (AGEP) presenting as septic shock. The disseminated, erythematous, pustular rash is a common feature. However, extensive organ involvement and life-threatening hypotension are unusual. The constellation of signs has not previously been documented following amoxicillin therapy. Toxic epidermal necrolysis (TEN) and toxic shock syndrome (TSS) were considered in addition to AGEP because of the systemic presentation. AGEP was diagnosed following histopathology (TEN was ruled out based on limited necrotic keratinocytes and lack of epidermal necrosis) and a negative antistreptolysin O titer (eliminated TSS). Antibiotic therapy for septic shock was provided before the diagnosis was confirmed as AGEP. Upon confirmation of the AGEP diagnosis, antibiotics were discontinued and a 5-day course of oral prednisone (40 mg/d) was initiated in addition to topical half-strength (0.05%) betamethasone valerate. The patient rapidly improved and was discharged. Outpatient patch testing confirmed amoxicillin as the culprit drug. In conclusion, it is critical to realize that AGEP cannot be ruled out with a septic shock presentation. Recent drug history is critical in recognizing an adverse drug reaction, and patch testing is useful for determining the culpable drug when the diagnosis is AGEP.